Carbamazepine poisoning: A narrow escape - Ryan Sohail Kaiser; Abhishek Dutta; Mihir Sarkar; Kalpana Datta (Wolters Kluwer Medknow Publications, 2020)
Carbamazepine is an anticonvulsant medication used in the treatment of focal epilepsy, neuropathic pain, and manic-depressive illness. Acute ingestion above the therapeutic range can lead to a range of manifestations ranging from the excessive somnolence to severe life-threatening multi-organ involvement. Here, we present one case of a 1 year-6 month-old girl who was brought to our hospital with a history of accidental ingestion of carbamazepine above therapeutic dose with features of the severe central nervous system impairment. After a stormy course in the pediatric intensive care unit, the child developed neurological sequele but improved after rehabilitation therapy.